Multiwalled Carbon Nanotube Synthesis Using Arc Discharge with Hydrocarbon as Feedstock - K. T. Chaudhary; Z. H. Rizvi; K. A. Bhatti; J. Ali; P. P. Yupapin (My University, 2013)
Synthesis of multiwalled carbon nanotube (MWCNT) by arc discharge process is investigated with methane (CH 4 ) as background and feedstock gas. The arc discharge is carried out between two graphite electrodes for ambient pressures 100, 300, and 500 torr and arc currents 50, 70, and 90 A. Plasma kinetics such as the density and temperature for arc discharge carbon plasma is determined to find out the contribution of physical parameters as arc current and ambient pressure on the plasma dynamics and growth of MWCNT. With increase in applied arc current and ambient pressure, an increase in plasma temperature and density is observed. The synthesized samples of MWCNT at different experimental conditions are characterized by transmission electron microscopy, scanning electron microscopy, Raman spectroscopy, Fourier transform infrared spectroscopy, and X‐ray diffraction. A decrease in the diameter and improvement in structure quality and growth of MWCNT are observed with increase in CH 4 ambient pressure and arc current. For CH 4 ambient pressure 500 torr and arc current 90 A, the well‐aligned and straight MWCNT along with graphene stakes are detected.
Keywords: Electric arc; Ambient pressure; Torr; Carbon Nanotubes in Composites